The Influence Of Social Media Usage And Key Opinion Leader (Kol) On Purchase Decisions At Fore Coffee With Purchase Intention As A Mediating Variable - Abdul Mughni; Ihwan Susila (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the influence of social media and Key Opinion Leaders (KOL) on purchase decisions, with purchase intention as a mediating variable. The research was conducted on Fore Coffee consumers using a quantitative research method, with primary data collected through an online questionnaire. Respondents consisted of the Soloraya community who had purchased Fore Coffee in the last six months.The results show that social media and KOL significantly influence purchase intention and purchase decisions. Moreover, purchase intention is proven to be a significant mediator in the relationship between social media and KOL with purchase decisions. This study implies the importance of social media-based marketing strategies and KOL in increasing consumer purchase intention and decisions.